Myths about suicide - Joiner, Thomas (New York Harvard University Press, 2010)
We need to get it in our heads that suicide is not easy, painless, cowardly, selfish, vengeful, selfmasterful, or rash; that it is not caused by breast augmentation, medicines, "slow" methods like smoking or anorexia, or, as some psychoanalysts thought, things like masturbation; that it is partly genetic and influenced by mental disorders, themselves often agonizing; and that it is preventable and treatable.
Introduction : our most basic terror and our most tragic thoughts -- The suicidal mind -- Suicidal behavior -- Causes, consequences, and subpopulations -- Conclusion : stigma : the future of a partial illusion.
Includes bibliographical references and index.
Keywords: Suicide; Suicide victims -- Psychology